Hippocratic Commentaries in the Greek, Latin, Syriac and Arabic Traditions : Selected Papers from the XVth Colloque Hippocratique, Manchester - Pormann, Peter (Studies in Ancient Medicine, 2021)
This collection of article presents cutting-edge scholarship in Hippocratic studies in English from an international range of experts. It pays special attention to the commentary tradition, notably in Syriac and Arabic, and its relevance to the constitution and interpretation of works in the Hippocratic Corpus. It presents new evidence from hitherto unpublished sources, including Greek papyri and Syriac and Arabic manuscripts. It encompasses not only the classical period (and notably Galen), but also tackles evidence from the medieval and Renaissance periods. Contributors are: Elizabeth Craik, David Leith, Tommaso Raiola, Jacques Jouanna, Caroline Magdelaine, Jean-Michel Mouton, Peter N. Singer, R. J. Hankinson, Ralph M. Rosen, Daniela Manetti, Mathias Witt, Amneris Roselli, Véronique Boudon-Millot, Sabrina Grimaudo, Giulia Ecca, Kamran I. Karimullah, María Teresa Santamaría Hernández, and Jesús Ángel y Espinós.